From Song to Loyalty: How the Anthem of Universitas Trunojoyo Madura Enhances Student Engagement and Strengthens Institutional Bonds - Saksono, Suryo Tri (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2024)
University anthems, as key elements in shaping the identity of higher education institutions, reflect the values and history of the university and enhance a sense of community. This study focuses on how the integration of traditional Madurese elements in the anthem of Universitas Trunojoyo Madura influences student identity and engagement. The knowledge gap lies in the actual influence of traditional music in enhancing student engagement and loyalty. A qualitative methodology was employed, involving in-depth interviews and lyrical content analysis of the anthem to uncover student perceptions. The primary findings suggest that the use of traditional Madurese music elements enhances student pride and engagement, strengthens institutional identity, and reinforces community bonds. The implications of these findings affirm the crucial role of arts and literature in facilitating social and communal engagement in academic settings, providing new insights for the development of educational strategies and university policies.